Peter Pan in scarlet - McCaughrean, Geraldine (Margaret K. McElderry Books, 2006)
In the 1930s, all is not well. Nightmares are leaking out of Neverland. Fearing for Peter Pan's life, Wendy and the Lost Boys go back to Neverland -- with the help of the fairy Fireflyer -- only to discover their worst nightmares coming true! Peter Pan and his friends eventually restore Neverland to rights.